2021
DOI: 10.1016/j.jeurceramsoc.2020.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization kinetics of Al2O3-26mol%Y2O3 glass and full crystallized transparent Y3Al5O12-based nanoceramic

Abstract: Transparent Y 3 Al 5 O 12-based polycrystalline ceramics with excessive Al 2 O 3 composition (Al 2 O 3-26 mol%Y 2 O 3 , AY26) have been demonstrated as potential host materials for phosphor applications. However, the crystallization mechanism of AY26 glass has not been thoroughly investigated so far. In this work, the non-isothermal crystallization kinetics of AY26 glass was experimentally analyzed. The AY26 glass depicts high activation energy and crystallization mechanism of volume nucleation followed by thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Three equations can be summarized as lnfalse(α(TpT0)nfalse)${\rm{ln}}( {\frac{\alpha }{{{{( {{T_p} - {T_0}} )}^n}}}} )$ versus 1/Tp$1/{T_p}$ 38 . It is the Kissinger equation when n = 2, T 0 = 0 K; the Augis–Bennett equation when n = 1, T 0 = 300 K; the Ozawa equation when n = 0, T 0 = 0 K.…”
Section: Methodsmentioning
confidence: 99%
“…Three equations can be summarized as lnfalse(α(TpT0)nfalse)${\rm{ln}}( {\frac{\alpha }{{{{( {{T_p} - {T_0}} )}^n}}}} )$ versus 1/Tp$1/{T_p}$ 38 . It is the Kissinger equation when n = 2, T 0 = 0 K; the Augis–Bennett equation when n = 1, T 0 = 300 K; the Ozawa equation when n = 0, T 0 = 0 K.…”
Section: Methodsmentioning
confidence: 99%
“…As reported in Refs. [39,40], these bulk glass precursors were heated at 950-1300 ℃ for 2 h to perform full crystallization, i.e., to produce the transparent ceramics.…”
Section: Sample Preparationmentioning
confidence: 99%
“…There are two distinct phases, namely the dark phase and bright phase, which fuse with each other to form the whole ceramic materials. The grains of LuAG appear in a bright area due to the higher average atomic number ( LuAG Z ≈ 47.6), and a dark area is composed of the Al 2 O 3 grains with a lower average atomic number ( [39,40]. The in-line transmittance of the as-prepared transparent materials (1.0 mm in thickness) crystallized from the ALu28 glass-based precursors at 950, 1000, 1100, and 1200 ℃ for 2 h were measured in the UV-Vis-NIR and mid-infrared (MIR) regions, as shown in Fig.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The coating also maintained the original flat morphology, which showed that the ablation resistance of the ZrO 2 coating was higher than that of the Y 2 O 3 coating. Generally, the coated composites were less affected by ablation than the non-coated [25], although both the Y 2 O 3 and Al 2 O 3 had a very high melting point, it was easy for them to form eutectic compounds with different percentages of Y 2 O 3 . Thus, at around 1900°C, the melting of eutectic compounds could be observed.…”
Section: Ablation Behaviour Of Coated Al 2 O 3f /Al 2 O 3 Compositesmentioning
confidence: 99%